Is translation a linguistic or a cultural process? - Hans Vermeer (Ilha do Desterro)
The English term "linguistic" has a general and a special meaning. In ordinary or standard language "Gemeinsprache") linguistic means "of language", "belonging to language" ("sprachlich"), language taken in its everyday meaning, as in English language, German language etc. Thus, an expression like a linguistic sign may be paraphrased by a sign of language or, in more technical language, a verbal sign ("ein sprachliches Zeichen"), something one says or writes. Language has another, broader, almost metaphorical meaning when one speaks, for instance, of the language of animals or the language of nature. Language in such cases means any system of signs.